Effects of cold‐water corals on fish diversity and density (European continental margin: Arctic, NE Atlantic and Mediterranean Sea): Data from three baited lander systems. (November 2017) - Linley, T.D.; Lavaleye, M.; Maiorano, P.; Bergman, M.; Capezzuto, F.; Cousins, N.J.; D'Onghia, G.; Duineveld, G.; Shields, M.A.; Sion, L.; Tursi, A.; Priede, I.G.
Abstract: Autonomous photographic landers are a low-impact survey method for the assessment of mobile fauna in situations where methods such as trawling are not feasible or ethical. Three institutions collaborated through the CoralFISH project, each using differing lander systems, to assess the effects of cold‐water corals on fish diversity and density. The Biogenic Reef Ichthyofauna Lander (BRIL, Oceanlab), Autonomous Lander for Biological Experiments (ALBEX, NIOZ) and the Marine Environment MOnitoring system (MEMO, CoNISMa) were deployed in four CoralFISH European study regions covering the Arctic, NE Atlantic and Mediterranean, namely Northern Norway (275–310 m depth), Belgica Mound Province (686–1025 m depth), the Bay of Biscay (623–936 m depth), and Santa Maria di Leuca (547–670 m depth). A total of 33 deployments were carried out in the different regions. Both the time of first arrival ( T arr ) and the maximum observed number of fish (MaxN) were standardised between the different lander systems and compared between coral and reference stations as indicators of local fish density. Fish reached significantly higher MaxN at the coral stations than at the reference stations. Fish were also found to have significantly lower T arr in the coral areas in data obtained from the BRIL and MEMO landers. All data indicated that fish abundance is higher within the coral areas. Fish species diversity was higher within the coral areas of Atlantic Ocean while in Northern Norway and Santa Maria di Leuca coral areas, diversity was similar at coral and reference stations but a single dominant species ( Brosme brosme and Conger conger respectively) showed much higher density within the coral areas. Indicating that, while cold-water coral reefs have a positive effect on fish diversity and/or abundance, this effect varies across Europe׳s reefs.